The role of dietary diversity and other factors to stunting among infants and toddlers in West Java, Indonesia - Surmita Surmita; Rini Sekartini; Aria Kekalih; Dian Novita Chandra (Egyptian Pediatric Association Gazette)
Abstract Background Stunting is a major public health issue affecting infants and toddlers, characterized by impaired growth due to chronic malnutrition. This study aimed to examine the relationship between minimum dietary diversity (MDD) and other factors associated with stunting in infants and toddlers in West Java, Indonesia. Methods This study used data from the 2022 Indonesian Nutritional Status Survey, including 6700 children aged 6–59 months. The main variables analyzed were stunting, MDD, age of child, sex of child, low birth weight (LBW), continued breastfeeding, food security, maternal occupation, and social health insurance. Data were analyzed using IBM SPSS Statistics version 27. Multiple logistic regression with complex sampling analysis was applied to account for survey weighting and ensure representativeness. Results Four multivariate analysis models were developed. The primary multivariate model (Model I) revealed that inadequate MDD was significantly associated with stunting (adjusted odds ratio (aOR) = 1.52, 95% CI = 1.27–1.82, p < 0.001), even after adjusting for the child’s age, sex of child, LBW, and continued breastfeeding. In the other three models, inadequate MDD consistently showed a significant association with stunting, even after adjusting for additional factors such as food security, social health insurance, and maternal occupation. Conclusion Inadequate MDD is significantly associated with stunting in infants and toddlers in West Java. Prevention should focus on improving dietary diversity through strengthened Infant and Young Child Feeding (IYCF) counselling, community nutrition classes, Posyandu-based education, promoting home gardening, and support for local markets to increase household access to diverse nutritious foods.